2009
DOI: 10.1002/jmri.21642
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of glomerular filtration rate from MR renography and tracer kinetic models

Abstract: Purpose: To compare six methods for calculating the single-kidney glomerular filtration rate (GFR) from T 1 -weighted magnetic resonance (MR) renography (MRR) against reference radionuclide measurements. Materials and Methods:In 10 patients, GFR was determined using six published methods: the Baumann-Rudin model (BR), the Patlak-Rutland method (PR), the two-compartment model without bolus dispersion (2C) and with dispersion (2CD), the three-compartment model (3CD), and the distributed parameter model (3C-IRF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 30 publications
4
62
1
Order By: Relevance
“…The order of magnitude agrees with that expected on the basis of theoretical considerations (40%, Eq. [9]), but the mean value is lower than expected. In view of the high precision with which tubular flow differences are detected in this study (SD 7.2%, 2SD 14.4%; Table 4), the deviation between theory and measurement (40-33 ¼ 7%) cannot be attributed to random measurement error.…”
Section: Filtrationmentioning
confidence: 54%
See 1 more Smart Citation
“…The order of magnitude agrees with that expected on the basis of theoretical considerations (40%, Eq. [9]), but the mean value is lower than expected. In view of the high precision with which tubular flow differences are detected in this study (SD 7.2%, 2SD 14.4%; Table 4), the deviation between theory and measurement (40-33 ¼ 7%) cannot be attributed to random measurement error.…”
Section: Filtrationmentioning
confidence: 54%
“…Low molecular weight gadolinium chelates have a predominantly renal elimination by glomerular filtration without any tubular secretion or reabsorption (7). These substances have similar pharmacokinetics as tracers like inulin, EDTA, or iodinated contrast agents, and therefore allow for glomerular filtration rate (GFR) assessment with magnetic resonance imaging (MRI) (8)(9)(10)(11)(12). One potentially confounding factor is the interaction of the contrast agent and serum proteins.…”
Section: Magneticmentioning
confidence: 99%
“…(2), b(t) denotes the concentration in vascular space. However, some researches [30][31][32][33][34] used the concentration in abdominal aorta to replace b(t), which obviously brings a big influence on calculating the parameters [19]. Some papers used coronal plane sampling [7,25] and postprocessing corrections and population-averaged AIF curves [35].…”
Section: Discussionmentioning
confidence: 99%
“…The reference GFR was obtained from 99mTc-DTPA renal scintigraphy [10,19,20]. All subjects underwent 99mTc-DTPA scintigraphy first and gadopentetate dimeglumine (Gd-DTPA) dynamic contrastenhanced MR examinations afterwards.…”
Section: Swine Subjectsmentioning
confidence: 99%
“…Bokacheva et al [51] recently compared six frequently applied compartment models. It has been reported that GFR calculation is strongly influenced by the applied model (e.g., two or three compartments) and the definition of the ROI (whole kidney parenchyma or solely renal cortex).…”
Section: Applicationsmentioning
confidence: 99%